Gas-Phase Hydrodesulfurization of JP-8 Light Fraction Using Steam Reformate - Huang, Xiwen; King, David L (Industrial & engineering chemistry research, 2006)
Gas-phase hydrodesulfurization of a JP-8 light fraction was investigated over CoMo/Al2O3 and NiMo/Al2O3 catalysts. Use of a light fraction provides a fuel that is more easily desulfurized and allows the process to operate in the vapor phase. This study investigated the utilization of reformate (syngas) from a steam reformer rather than pure H2 as gas feed to HDS unit. This is consistent with what might be available to the military during operation in the field. Dry syngas functions almost as well as pure H2 in the HDS reaction, and sulfur levels below 5 ppmw are readily obtained from a feed initially containing 320 ppmw sulfur. Addition of 40 vol % steam to the syngas has a significant negative impact on HDS performance with CoMo/Al2O3, but only a small effect with NiMo/Al2O3. The impacts of various process conditions on S removal efficiency were examined and will be described.